Pandemic as a necropolitics trigger in a short story by Gabriela Rábago Palafox - Gutiérrez Hibler, Jonathan (2023)
The following paper analyses a short story written by the Mexican writer Gabriela Rábago Palafox. It starts defining the concept of necropolitics, by Mbembe (2011), and description as a macroperative phenomenon in narrative discourse, as Luz Aurora Pimentel understands as a expansion phenomenon of the text. From this theory, the paper shows and describes different passages from the short story “Pandemia” to see the equivalences of nomenclatures and its contradistinction with the social and political discourse that discriminates lots of sectors by using its own definition of the word disease. Later, a contrast is done between the passages to show the expansion of the text. One of the results of this investigation exhibits how a short story proposes a side scrolling lecture that ironizes the mechanism of exclusion used by the hegemonic powers in this represented discourse.